2021
DOI: 10.3390/plants10040759
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Improves Soil-Tomato Plant, Tomato Production, and Economic Benefits under Reduced Nitrogen Application in Northwestern China

Abstract: The tomato is an important economic crop that is a main ingredient of some prepared food as well as a focus of the agricultural industry. Optimizing nitrogen (N) fertilizers is essential for sustainable agricultural development, while the excessive use of N fertilizers leads to environmental and food production problems. As a soil amendment, biochar has been widely used to improve soil quality and crop yield. However, little information is available on the effects of biochar and N fertilizer reduction on tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…This investigation revealed that the addition of biochar enhanced crop production by improving soil physical and chemical properties [47], with positive and negative effects depending on soil texture, which agrees with Sohi et al [15]. Other studies, carried out in tomato crops, have also reported a relationship of crop yield to water and nutrient retention capabilities [5,6], soil aeration [8], and pH enhancement [48].…”
Section: Discussionsupporting
confidence: 88%
“…This investigation revealed that the addition of biochar enhanced crop production by improving soil physical and chemical properties [47], with positive and negative effects depending on soil texture, which agrees with Sohi et al [15]. Other studies, carried out in tomato crops, have also reported a relationship of crop yield to water and nutrient retention capabilities [5,6], soil aeration [8], and pH enhancement [48].…”
Section: Discussionsupporting
confidence: 88%
“…Most studies were performed in tropical and temperate zones of America, Asia, and Oceania, with no shortage of rain and even with a risk of flooding. Nevertheless, Guo et al reported yield improvements of up to 60% when using application rates of 30, 50, and 70 t/ha, fundamentally due to biochar interference in the fixation of supplemented nutrients and nutrient exchange in the soil-plant system [55]. In these temperate zones, other authors have reported results ranging from no improvement to slight improvements of 10% in tomato yield [56,57].…”
Section: Biochar Effect On Tomatomentioning
confidence: 99%
“…Moreover, the addition or application of organic or inorganic solutes may alter plant water relations. For example, Guo et al. (2021a) reported improved root hydraulic conductance and leaf water potential (Ψl) in water-stressed tomato grown on a sandy loam soil incorporated with miscanthus straw BC.…”
Section: Biochar Regulates Plant Water Nutrient Relations and Enhance...mentioning
confidence: 99%